PENYULUHAN KEWIRAUSAHAAN KEPADA PARA SISWA SMK MUHAMMADIYAH 1 BANDUNG - Ahmad Husen; Evie Farida Juliarta; Nelli Novyarni (JOURNAL OF COMMUNITY DEDICATION, 2024)
Entrepreneurship is a field that is still unfamiliar to vocational high school students. The process of introducing and understanding entrepreneurship needs to be encouraged early on. Many students are still confused about the function and values of entrepreneurship. To introduce entrepreneurship, counseling and reinforcement are needed for students at school. Community service activities are carried out so that students have a good interest in entrepreneurship. The method of activity is counseling with theoretical and practical materials. This activity was attended by 35 students at SMK Muhammadiyah 1 Bandung. The results of the activity, students were able to understand the importance of the role of entrepreneurship. It is hoped that students after completing their education can become reliable and responsible entrepreneurs later. Entrepreneurship can be one of the skills that can explore students' potential and play an important role in students' lives in the future. The purpose of community service is to provide insight and increase interest in entrepreneurship in vocational high schools to know about entrepreneurship. The application of this entrepreneurial spirit for vocational high school students is still considered difficult, because the education they take sometimes mentally they are not ready to enter the world of entrepreneurship. In developing this entrepreneurial spirit, high interest is needed. A strong interest in entrepreneurship will encourage students to be brave in entrepreneurship, because with this interest students feel they have the strength and ability to lead them to become successful entrepreneurs. But on the other hand, if the student does not have an interest in entrepreneurship, then the student will be afraid to develop his skills and will not be able to become a successful entrepreneur. In developing an entrepreneurial spirit in vocational high school students, not only skills education is needed, another factor that is no less interesting is the introduction of material about entrepreneurship which is indeed very much needed by vocational high school students.